Weed Interference Periods and Transplanting Densities of Onion Crop in the Brazilian Region of Guarapuava, PR1 - SOUZA,J.I. (2016)
ABSTRACT The study was conducted with the objective of determining the critical periods of interference prevention (CPIP) and the best period for the management of weeds community in onion crop Crioula Mercosul genotype, transplanted in distinct plants densities. The experiment was carried out in field conditions in the Brazilian municipality of Guarapuava, Paraná State, during the 2012 and 2013 agricultural years, at Universidade Estadual do Centro-Oeste - UNICENTRO. Treatments were disposed in randomized complete blocks and experimental design, with five repetitions, consisting of weeds coexistence periods and weeds control at 14, 28, 56, 112 and 168 days after transplanting the seedlings (DATS), using 0.6, 0.8 and 1.0 million plants ha-1. Weeds community was evaluated through a phytosociological survey at the end of each coexistence period in relation to yield and commercial quality of bulbs. Bulbs yield of transplanted onion was significantly affected by weeds coexistence, reaching 100% of losses. From adjusted models, viability was not observed in increasing plantation density as a practice that may favor the necessary reduction of weeds control. Onion plants transplanted in August 2012 and July 2013 presented CPIP, respectively, of 23 at 76 and 21 at 120 DATS for commercial bulbs yield, and of 20 at 55 and 26 at 112 DATS for total bulbs yield, respectively.